Environmental, social and corporate governance-esg e as implicações na política de dividendos - Nicácio, Antonio Gustavo (Universidade do Vale do Rio dos Sinos, 2023)
This study aimed to analyze whether the impact of ESG controversy scores explains a greater distribution of dividends and strengthens the legitimization of the management of these companies before their investors. Using descriptive statistics, correlations and Multiple Regressions, to respond to the objectives, financial performance data was collected from publicly traded companies in Economática®, such as ROA, ROE, Size, Age, Financial and operational leverage, and ownership concentration, and the scores ESG, combined ESG, social ESG, ESG, environmental and ESG governance, in the Thonsom Reuters Refinitiv database, in a time frame from 2017 to 2021. The sample was composed of 102 companies, which received the ESG score and controversies in certain periods. Using multiple regression, the hypothesis was tested that companies with ESG scores, which have suffered controversial events, distribute more dividends, to legitimize the company's management before investors. The result obtained refutes the hypothesis and, therefore, it is not possible to state whether there is a relationship between the ESG controversy and a greater distribution of dividends, as the result proved to be statistically insignificant.
Keywords: ESG; Social; Governança; Ambiental e dividendos; Governance; Environmental and dividends; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis